Comparison of the Signal Intensity of Vestibular Schwannoma Between Growing and Nongrowing Tumors. (20th August 2021) - Yamada, Hiroyuki; Kai, Naruhiko; Hiratsuka, Yoshiyasu; Mitani, Sohei; Suehiro, Satoshi; Shiraishi, Yasuhiro; Kimura, Takuya; Takagi, Taro; Iwata, Shinji; Teraoka, Masato; Wakisaka, Hiroyuki; Hato, Naohito
Abstract : Objectives/Hypothesis: To determine the relationship between signal intensity on gadolinium (Gd)‐enhanced magnetic resonance images and growth of vestibular schwannomas (VSs). Study Design: Cross‐sectional study. Methods: In this cross‐sectional study, we retrospectively reviewed the data of 31 patients with VSs who underwent magnetic resonance imaging (MRI). The mean signal intensities within the regions of interest in the tumor, pons, and temporal muscles were measured on Gd‐enhanced T1‐weighted MRI. Relative intensity ratios were calculated as follows: T / N pons ratio ( T /Np) is the tumor signal intensity/pons signal intensity and T / N muscle ratio ( T /Nm) is the tumor signal intensity/temporal muscle signal intensity. Volume measurements were used to assess the tumor size. Growth rate was determined by assessing previous imaging studies. Growing VS was defined as a tumor with a growth rate >100 mm 3 /year. Results: The mean (standard deviation) T /Np and T /Nm were 1.47 (0.27) and 1.50 (0.24), respectively, in nongrowing tumors and 1.78 (0.17) and 1.90 (0.12), respectively, in growing tumors. The T /Np and T /Nm differed significantly between the two groups ( T /Np, P < .001; T /Nm, P < .001). Receiver operating characteristic curve analysis showed that cutoffs of 1.56 and 1.76 for T /Np (93.33% sensitivity, 75.00% specificity) and T /Nm (100.00% sensitivity, 93.75% specificity), respectively, could be used to diagnose a growth rate of >100 mm 3 /year. The area under the curve was 0.85 (95% confidence interval, 0.70–1.00) for T /Np and 0.94 (0.82–1.00) for T /Nm. Conclusion: Growing VSs show higher signal intensities on Gd‐enhanced MRI. Thus, measuring the signal intensity of VS on Gd‐enhanced MRI may aid in predicting VS growth. Level of Evidence: 3 Laryngoscope, 132:198–203, 2022